An Analysis Of Figurative Language In The Wish Movie - Indah Ayu, Dewi Mutiara; Simanjuntak, Herlina Lindaria (PT Maju Malaqbi Makkarana, 2025)
Figurative language plays a significant role in enriching storytelling and enhancing the emotional impact of animated films. Wish, as a fantasy-animated film, incorporates various forms of figurative language to convey deeper meanings and strengthen the narrative. This study aims to analyze the types, meanings, and effects of figurative language used in the film Wish. Using a qualitative descriptive method, the research identifies and classifies different figurative expressions, including metaphors, similes, personifications, and hyperboles, within the film’s dialogues. The findings indicate that figurative language serves multiple functions, such as character development, emotional engagement, and thematic reinforcement. Moreover, it enhances viewers' comprehension and emotional connection with the story. The study also highlights how figurative language contributes to the moral and philosophical messages conveyed in the film. The results suggest that the creative use of figurative language in animated films not only improves aesthetic appeal but also aids in effective communication with audiences, particularly children. This research provides valuable insights for linguists, educators, and filmmakers on the importance of figurative language in cinematic storytelling. Future research can further explore audience reception and cross-cultural interpretations of figurative language in animated films.